THE POLITENESS EXPRESSED BY THE CHARACTERS IN “BEAUTY AND THE BEAST” MOVIE PRODUCED BY WALT DISNEY - Imanila Imanila; Hendra Hendra; Sisca Wulansari Saputri (FKIP, Universitas Banten Jaya, 2019)
This study is focused on analysis of the politeness expressed by the main characters and supporting characters in “Beauty and the Beast” Movie. The objective of this study are to know the politeness expressed by the main characters; Beauty (Belle) and the Beast (Prince) and to know the politeness expressed by the supporting characters in “Beauty and the Beast” movie. This Study is qualitative research that used content analysis method. Technique of data analysis in this study is using descriptive qualitative. The result of analysis are the sum of expression of politeness in saying thank you are 8 expressions, in saying hello are 7 expression, in answer the saying hello are 2 expressions, in use ‘I’m sorry’ are 5 expression and of how to sound more polite are 5 expressions. The sum of all expression of politeness that expressed by the characters in “Beauty and the Beast” movie are 27 expressions. Based on the discussion of the result of analysis, It can be concluded that expression of politeness is important in communication and it usually use in conversation when people in saying hello or greeting, when people answer the saying hello or greeting from others, when people ask with the sound more polite, and the last when people saying use ‘I’m sorry’ to refused and ignore something and ask to forgiven by other people. This study can be applied to conduct the learning material in teaching about the English expression in conversation, especially expression of politeness.